GE_GERICHTE P/10891/2014 vom 28. Mai 2015 - GE Cour de justice (2015)
SÉJOUR ILLÉGAL; FIXATION DE LA PEINE; SÉQUESTRE(MESURE PROVISIONNELLE); SUPPRESSION(EN GÉNÉRAL) | LEtr.115.1.b; CPP.263; CP.41.1; CPP.268.1